Xylodon bambusinus and X. xinpingensis spp. nov. (Hymenochaetales) from southern China - Ma, Xiang; Zhao, Chang-Lin (Phytotaxa, 2021)
Two new species, Xylodon bambusinus and X. xinpingensis, are proposed based on morphological and molecular evidences. Both species share the annual growth habit, resupinate basidiomata and monomitic hyphal system with clamped, colorless generative hyphae, smooth, thin-walled basidiospores, but X. bambusinus is characterized by the smooth to tuberculate hymenial surface, presence of capitate and fusiform cystidia, broad ellipsoid basidiospores, while X. xinpingensis by the reticulate hymenophore with cream hymenial surface, and subglobose basidiospores (4.5–6 × 3.5–5 µm). Sequences of ITS and LSU nrRNA gene regions of the studied samples were generated, and phylogenetic analyses were performed with maximum likelihood, maximum parsimony and Bayesian inference methods. The phylogenetic analyses based on molecular data of ITS and ITS+nLSU sequences showed that X. bambusinus was sister to X. subclavatus, while X. xinpingensis grouped with X. astrocystidiatus and X. paradoxus. The nLSU dataset revealed that X. bambusinus grouped with X. asperus and X. brevisetus with lower supports, and that X. xinpingensis grouped with X. astrocystidiatus and X. paradoxus and then with X. rimosissimus without supports. Both morphological and molecular evidences confirmed the placement of two new species in Xylodon. Description and figures from the new species and a key to the known species of Xylodon from China are presented.